2017
DOI: 10.3390/nu9030228
|View full text |Cite
|
Sign up to set email alerts
|

Partially Hydrolyzed Guar Gum Increases  Ferroportin Expression in the Colon of Anemic  Growing Rats

Abstract: Studies have reported a positive effect of prebiotics on the bioavailability of iron. This study evaluated the effect of partially hydrolyzed guar gum (PHGG) on iron absorption mechanisms in anemic rats. Male Wistar rats were fed 75g American Institute of Nutrition Rodent Diets for growth, pregnancy and lactation (AIN93-G) without iron for three weeks in order to induce iron deficiency anemia. Then they were fed a control diet (n = 12; without fiber) or a diet with 7.5% of PHGG (n = 12), both without iron. Foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
2
16
0
1
Order By: Relevance
“…The weights of colonic and cecal contents were involved in improving intestinal health [ 52 , 53 ]. Zhou et al [ 40 ] reported that the increase of the cecal content and cecal wall weight might result from the formation of SCFAs.…”
Section: Discussionmentioning
confidence: 99%
“…The weights of colonic and cecal contents were involved in improving intestinal health [ 52 , 53 ]. Zhou et al [ 40 ] reported that the increase of the cecal content and cecal wall weight might result from the formation of SCFAs.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal bleeding in patients with IBD increases iron loss. With the majority of iron being taken up in the duodenum through heme and nonheme iron transporters (elementary iron is reduced to Fe 2+ before uptake) with animal data showing some absorption from the large bowel as well [ 54 ], the iron enters the epithelial cells. Iron might be stored in the cells as mucosal ferritin or is exported to the circulation through the transporter, ferroportin and oxidized to Fe 3+ .…”
Section: Pathophysiology Of Anaemia In Ibdmentioning
confidence: 99%
“…Evidences point out several benefits in iron absorption from the ingestion of prebiotics [ 13 , 14 , 15 ]. Polydextrose (PDX), a highly branched and randomly linked glucose polymer with a mean degree of polymerization of 12, ranging from 2 to 120 and containing all possible combinations of 1→2, 1→3, 1→4 and 1→6 glycosidic bonds, with 1→6 (both α and β) predominating, has received special attention in iron metabolism and absorption [ 10 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%